Developing and Validating a Measurement Scale for Customer Social Responsibility in Green Financial Product Consumption: Evidence from Vietnamese Commercial Banks - Nhung, Nguyen Thi; Trung, Nguyen Xuan; Phuong, Nguyen Hoai (Journal of Cultural Analysis and Social Change, 2026)
This study develops and validates a multidimensional scale for the construct of Customer Social Responsibility (CuSR) in the context of green financial product consumption, thereby addressing an important measurement gap in the literature on sustainable finance and ethical consumption. Departing from prior approaches that primarily adapt scales from corporate social responsibility or generalized green consumption, this study reconceptualizes CuSR as an attitude–behavioral construct that is specific to financial decision-making processes. The construct emphasizes ethical responsibility, community-oriented value orientations, and value congruence between customers and socially responsible financial institutions. The scale was developed through a three-stage procedure (expert evaluation, EFA, and CFA). The findings confirm a theoretically consistent four-dimensional structure and provide strong evidence of reliability and construct validity (CR > 0.88; AVE > 0.60; HTMT < 0.85). Furthermore, tests of nomological and criterion validity indicate that CuSR is positively associated with green financial intention, trust in socially responsible banks, and the actual use of green financial products. Taken together, these results contribute to theory by introducing one of the first CuSR scales specifically standardized for the green finance context in an emerging market. The study also clarifies the conceptual boundary between responsible consumption and customers’ ethically oriented financial behavioral capability, thereby offering a robust measurement foundation for future comparative studies, model testing, and theoretical extensions.